Some Aspects of Women’s Health in Republic of Macedonia - Dimovska, Mirjana; Borota Popovska, Mirjana; Topuzovska Latkovikj, Marija; Pavleska Kuzmanoska, Svetlana; Gjorgjev, Dragan (Scientific Foundation SPIROSKI, 2022)
INTRODUCTION: Sex and gender “matters” in terms of the health status as well as a result of both biological and gender-related differences. Thus, sex must be considered in all aspects and all levels of biomedical research.AIM: This study aims to analyze sex- and gender-based differences in Republic of Macedonia through analysis of some aspects of mortality, the knowledge, and attitudes related to women’s health.METHODS: Analysis of the general and age-standardized mortality patterns and computer-assisted personal interview composed on different topics including women’s health for the period of 2017–2020 were used.RESULTS: Age-standardized mortality rates (all-causes of death, circulatory and respiratory diseases, and neoplasms) are prevalent and higher in the male population in Republic of Macedonia. A significantly higher all-cause mortality trend for both sexes was found in 2020 making this year hardly comparable with the previous years. A decreasing trend of malignant neoplasms rate of female genital organs and an increasing trend of breast cancer mortality is observed. The majority of the respondents (50.6%) rated their current health status as excellent with a statistically significant difference between the age and ethnical groups. One-third of the respondents reported regular physical activity, mostly on a daily basis. The majority (39.3%) are overweight and 27.5% belongs to the obesity Class I without a significant difference in terms of ethnicity. Respondents (27%) reported that have high blood pressure, 20.2% vaginal infections, 19.9% allergies, heart issues 15.1%, anemia 11.7%, while diabetes and cancer 8.5% and 2.5%, respectively. The youngest and oldest age groups of Albanian women are the least informed about the early detection procedures of malignant compared to Macedonian women and other ethnic groups.CONCLUSIONS: Analyzing some aspects of women’s health in Republic of Macedonia through the mortality and knowledge and attitudes of Macedonian women, we provide some further evidence for the development and implementation of targeted interventions and policies aimed to reduce the sex- and gender-based health inequalities in the country.
Keywords: Women’s health; Macedonia; Mortality patterns; Computer-assisted personal interview